Navigating the Future: Trends Shaping IT Industry - Dr. A. Geetha; Mahesh Prabu Arunachalam (International Journal of Engineering and Management Research, 2024)
This abstract explores emerging trends in shaping the IT industry’s future. From artificial intelligence and cybersecurity to decentralized technologies, it delves into the transformative forces guiding IT professionals and businesses toward innovative landscapes. By navigating these trends strategically, the industry can harness new opportunities and overcome challenges in an ever-evolving technological landscape.